2003
DOI: 10.1185/030079902125001380
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience with a high bolus dose of tirofiban during percutaneous coronary intervention

Abstract: The use of a high bolus dose of tirofiban in patients undergoing PCI seems to be safe and not associated with an increased risk of major bleeding. This high bolus dose may help to further reduce the rate of periprocedural adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Our results are in accordance with earlier observations during treatment with (high-dose bolus) tirofiban (11,12). Study limitations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in accordance with earlier observations during treatment with (high-dose bolus) tirofiban (11,12). Study limitations.…”
Section: Discussionsupporting
confidence: 94%
“…Improving platelet aggregation inhibition by increasing the bolus dose of the glycoprotein (GP) IIb/IIIa inhibitors has been described in patients undergoing elective or high-risk PCI and in patients with non-ST-segment elevation myocardial infarction (7)(8)(9)(10). This was not associated with an increased risk of major bleeding (11,12). In patients with ST-segment elevation myocardial infarction (STEMI), routine dose of antiplatelet agents may be associated with less effective platelet aggregation inhibition.…”
mentioning
confidence: 97%
“…Recently, Schneider et al (5) have identified a tirofiban bolus of 25 g/kg (followed by maintenance infusion of 0.15 g/kg/min) that achieves inhibition of platelet aggregation Ͼ85% through 60 min. Preliminary reports have documented safety and efficacy of this dose regimen in patients undergoing elective or high-risk PCI (6,7). The role of this regimen in high-risk patients with NSTE-ACS remains to be established.…”
Section: See Page 538mentioning
confidence: 97%
“…However, they used a much lower PPACK concentration and they did not compare citrate and PPACK. Danzi et al [23] showed in 133 consecutive patients that tirofiban given with a bolus of 25).ig/kg and an infusion of 0.15|.ig/kg per min was not associated with an increased risk of major bleeding.…”
Section: Discussionmentioning
confidence: 98%